1996
DOI: 10.1007/s002640050067
|View full text |Cite
|
Sign up to set email alerts
|

Determination of periprosthetic bone density with the DEXA method after implantation of custom-made uncemented femoral stems

Abstract: Implantation of a total hip replacement leads to resorption of bone, especially in the upper femoral shaft and this depends mainly on the design of the stem, and also on the survival time of the implant. Density of the periprosthetic bone was examined with the DEXA method in both femurs in 27 patients at a mean of 21 months after implantation of uncemented custom-made femoral stems. A loss of bone density between 5% and 21% was found which was independent of the survival time of the implant. The maximum decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
3
26
1
Order By: Relevance
“…Therefore, the use of frontal-plane regions of interests like the Gruen zones is not suitable for qCT. Several studies have reported the highest levels of BD resorption in Gruen zones 1 or 7, which corresponds with our most proximal scan around the greater trochanter and femoral neck, where we also found the highest levels of cancellous and cortical BD loss (ROI 1 and 2) [5,10]. Other studies have reported a BD loss of greater than 50% in the calcar region [14,25].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Therefore, the use of frontal-plane regions of interests like the Gruen zones is not suitable for qCT. Several studies have reported the highest levels of BD resorption in Gruen zones 1 or 7, which corresponds with our most proximal scan around the greater trochanter and femoral neck, where we also found the highest levels of cancellous and cortical BD loss (ROI 1 and 2) [5,10]. Other studies have reported a BD loss of greater than 50% in the calcar region [14,25].…”
Section: Discussionmentioning
confidence: 52%
“…Finiteelement analyses showed that the extent of stress shielding is directly correlated to stem stiffness, with lower E-modulus materials like titanium-reducing proximal stress shielding [6,21]. HA-coated implants show a good clinical and radiological outcome with moderate BD loss and improved implant fixation when compared with porous-coated implants [10,18,20]. Histological analyses in cadaveric specimens have shown sound proximal and distal HA stem-bone osteointegrations in a relatively short period after THA [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, while only two-dimensional surface determinations are possible with conventional DXA, three-dimensional assessment of the bone is possible with CT-assisted osteodensitometry. In the present study using CT-assisted bone mineral densitometry, less bone resorption (approximately -20% for cortical and cancellous BD) was found in the proximal part of the femur when compared to similar measurements made with DXA (-35% for Gruen zones 1 and 7) [7,8]. These findings probably result from the type of implant used in our study, particularly its tapered design.…”
Section: Discussionsupporting
confidence: 35%
“…Tapered femoral components had a proximal loss between 10% to 30% [1,6,19]. Custommade implants reported the best results regarding the proximal loss of BMD, but with a fall of between 10% to 15% at the end of the third year [12,13]. Recently, femoral stems with reduced stiffness showed a 15% reduction of BMD in the calcar at the end of the second year [7,9,16].…”
Section: Discussionmentioning
confidence: 99%